A comparison of patient-controlled analgesia with oxycodone and morphine after total abdominal hysterectomy surgery - Chen JL,; Rufinah T,; Fadzlon Mohd Yatim,; Liu, Chian Yong; Omar S,; Mahazir K, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
We compared the analgesic profile between patient-controlled analgesia (PCA) using oxycodone and morphine in post total abdominal hysterectomy patients. Eighty-four ASA I or II patients, aged 18 to 65 years who underwent total abdominal hysterectomy were recruited into this prospective, double blind, randomised controlled study. They were randomised to receive either PCA oxycodone 0.7 mg per bolus or PCA morphine 1 mg per bolus for postoperative pain relief. At the end of surgery, all patients received IV morphine 0.1 mg/kg and skin incision was infiltrated with 20 mls of bupivacaine 0.25%. Post-operative pain scores, opioids consumptions, sedation scores and side effects were assessed upon arrival and at 30 minutes after arrival to recovery area, as well as at 6 hours and 24 hours after the operation in the ward. Patients’ overall satisfaction was also assessed 24 hours postoperatively.No significant differences were observed in terms of postoperative pain scores, opioids consumption, sedation scores, side effects as well as patient’s overall satisfaction between the PCA oxycodone and PCA morphine group. Oxycodone was comparable to morphine as PCA in terms of total opioid consumption, pain scores and satisfaction level for patients undergoing total abdominal hysterectomy and therefore may be an alternative to morphine in postoperative pain management as PCA.